Contemporary Library Networks in India: A Survey - Jana, Arup (International Journal of Computer Sciences and Engineering, 2015)
Library is a store-house of information, documentation, audio-visual and graphic materials stored in a variety of media ranging from printed books, periodicals, posters and report, microforms, slides, films, videos, audio, discs, audio-tapes, optical discs, magnetic tapes, floppy discs etc. Electronic Library is likely to be part of a network. An electronic Library deals with both house-keeping operations like acquisitions, catalogue creation, circulation control, serial control, Online Public Access Catalogue (OPAC) and the generation of management information and information retrieval systems like external databases and associated services and products and internal or local databases and their associated services and products. These are Current Awareness Services (CAS), Selective Dissemination of Information (SDI) etc. Application of new information technology has brought in dramatic changes in the library and information field. With technological advancement, libraries and information centres around the world have computerised their library routines and have developed databases for shared use on computer networks. Besides improving services and operations for improving performance, libraries have also been able to evolve effective computer networks with an aim to optimize utilization of resources and facilities. The library and information networks have potential to improve library services in several ways. It brings down the cost of information products and services in the network environment in shared mode. It enables libraries to offer need based services to the end users eliminating the limitation of size, distance and language barriers among them. With evolution in library networks the emphasis has moved from the networks as physical entities to the resources available through the networks. These network accessible resources as include databases of library holdings, journal articles, electronic text, images, video and audio files, scientific and technical data etc.